The Effectiveness of Career Information Services with CEV Media on Elementary School Students - Agus Basuki; Ridwan Kurniawan (Jurnal Prima Edukasia, 2022)
This study aims to determine the understanding of career information services with CEV (Career Education Video) in elementary school students. This research method is an experimental design with a quasi-experimental type of Nonequivalent Control Group Design. The subject of this research is class VI. The instrument used is the student career information scale. The research stages are pretest, treatment, andposttest. The experimental class gets service with CEV Media, while in the control class it is conventional/lecture. The analysis of research data with parametric statistics using the independent sample t-test. The results of the study indicate that there is a difference in the average value of career maturity in the two groups. The difference that occurs is 5.10 with details of 104.23 in the control class and 109.13 in the experimental class. The results of the hypothesis test show that the results are significant. This studyconcludes that service delivery with CEV Media is effective in providing career information for elementary school students.